Diagnostic value of quantitative parameters for myocardial perfusion assessment in patients with suspected coronary artery disease by single- and dual-energy computed tomography myocardial perfusion imaging. (February 2021) - Ruiz-Muñoz, Aroa; Valente, Filipa; Dux-Santoy, Lydia; Guala, Andrea; Teixidó-Turà, Gisela; Galián-Gay, Laura; Gutiérrez, Laura; Fernández-Galera, Rubén; Casas, Guillem; González-Alujas, Teresa; Ferreira-González, Ignacio; Evangelista, Arturo; et al.
Abstract: Purpose: To compare performance of visual and quantitative analyses for detecting myocardial ischaemia from single- and dual-energy computed tomography (CT) in patients with suspected coronary artery disease (CAD). Methods: Eighty-four patients with suspected CAD were scheduled for dual-energy cardiac CT at rest (CTA) and pharmacological stress (CTP). Myocardial CT perfusion was analysed visually and using three parameters: mean attenuation density (MA), transmural perfusion ratio (TPR) and myocardial perfusion reserve index (MPRI), on both single-energy CT and CT-based iodine images. Significant CAD was defined in AHA-segments by concomitant myocardial hypoperfusion identified visually or quantitatively (parameter < threshold) and coronary stenosis detected by CTA. Single-photon emission CT and invasive coronary angiography were used as reference. Perfusion-parameter cut-off values were calculated in a randomly-selected subgroup of 30 patients. Results: The best-performing thresholds for TPR, MPRI and MA were 0.96, 23 and 0.5 for single-energy CT and 0.97, 47 and 0.3 for iodine imaging. For both CT-imaging modalities, TPR yielded the highest area under receiver operating characteristic curve (AUC) (0.99 and 0.97 for single-energy CT and iodine imaging, respectively, in vessel-based analysis) compared to visual analysis, MA and MPRI. Visual interpretation on iodine imaging resulted in higher AUC compared to that on single-energy CT in per-vessel (AUC: 0.93 vs 0.86, respectively) and per-patient (0.94 vs 0.93) analyses. Conclusion: Transmural perfusion ratio on both CT-imaging modalities is the best-performing parameter for detecting myocardial ischaemia compared to visual method and other perfusion parameters. Visual analysis on CT-based iodine imaging outperforms that on single-energy CT.